2020
DOI: 10.1186/s12964-020-00628-4
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of dysregulated Hh-FOXM1-TPX2 signaling in human hepatocellular carcinoma cell proliferation

Abstract: Background: Aberrant activation of the Hedgehog (Hh) signaling pathway is frequently observed in hepatocellular carcinoma (HCC), nevertheless, the precise molecular mechanism remains unclear. Forkhead box M1 (FOXM1), a target of the Hh pathway, is a key oncofetal transcription factor and a master cell cycle regulator. Targeting protein for Xenopus kinesin-like protein 2 (TPX2) is an oncogene critical for mitosis. However, how these molecular events affect HCC progression remains unclear. Methods: Realtime PCR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Therefore, we propose that other cues to activate BCL2L1 promoter activity such as YAP1 activation would be required to confer the cells with the survival advantage trait (e.g., YAP1 stabilization by Aurora-A activity due to TPX2 induction). A recent study demonstrated that the Hedgehog signal is responsible for TPX2 induction through the FOXM1 transcription factor in cancer cells [30]. Considering the complexity of the YAP1 activation mechanism, we could not rule out the role of other events (e.g., Factin stabilization [24]) in YAP1 activation for culture adaptation of hESCs other than the TPX2-Aurora-A axis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, we propose that other cues to activate BCL2L1 promoter activity such as YAP1 activation would be required to confer the cells with the survival advantage trait (e.g., YAP1 stabilization by Aurora-A activity due to TPX2 induction). A recent study demonstrated that the Hedgehog signal is responsible for TPX2 induction through the FOXM1 transcription factor in cancer cells [30]. Considering the complexity of the YAP1 activation mechanism, we could not rule out the role of other events (e.g., Factin stabilization [24]) in YAP1 activation for culture adaptation of hESCs other than the TPX2-Aurora-A axis.…”
Section: Discussionmentioning
confidence: 89%
“…2D). Considering the roles of TPX2 in cancer malignancy [30] and survival/chemoresistance [31], it is readily presumed that TPX2 expression may be associated with BCL2L1 induction and consequent survival traits. As predicted, depletion of TPX2 in P4 hESCs signi cantly attenuated BCL2L1 expression (Fig.…”
Section: Bcl2l1 Induced Survival Associated With Tpx2mentioning
confidence: 99%
“…Tumor tissues collected from mice were fixed in 10% neutral-buffered formalin solution, dried, and embedded in paraffin blocks, which were subsequently cut into 3-ÎŒm-thick sections for IHC staining ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…The genetic abrogation of TPX2 in mouse embryos leads to arrest at the morula stage and early embryonic lethality due to the incorrect formation of bipolar spindles [31] and the missegregation of chromosomes, implying that critical roles of TPX2 in early embryonic development [32]. On the other hand, the ectopic expression TPX2 is su cient to induce polyploidy [33] and elevates malignancy in cancers [34]. Considering the strong association of TPX2 expression with CIN in cancer [35], and with poor patient survival in various forms of cancers [28,34], the deregulation of TPX2 is a putative driver of CIN by accelerating aberrant mitotic spindle dynamics and improper chromosome segregation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the ectopic expression TPX2 is su cient to induce polyploidy [33] and elevates malignancy in cancers [34]. Considering the strong association of TPX2 expression with CIN in cancer [35], and with poor patient survival in various forms of cancers [28,34], the deregulation of TPX2 is a putative driver of CIN by accelerating aberrant mitotic spindle dynamics and improper chromosome segregation.…”
Section: Introductionmentioning
confidence: 99%